Diagnostic accuracy of serum lipase and amylase as biomarkers for acute pancreatitis - Kumar, Anil; Kapoor, Sangeeta (International Journal of Research in Medical Sciences, 2018)
Background: Currently, majority of clinicians ask for both amylase and lipase for diagnosis of acute pancreatitis but a large number of health care facilities in India still have facility for only amylase. Aim was to find which single marker to be used in for diagnosis of acute pancreatitis. Methods: Patients seeking care at emergency department for acute abdominal pain during the period from July 2016 to June 2017 formed the study population. The serum lipase and amylase were taken from 1725 patients. Diagnostic accuracy, sensitivity, specificity, positive and negative predictive values and positive and negative likelihood ratios were calculated. Results: Sixteen patients had amylase above 3-fold elevation, while there were 26 such patients in the lipase group. The sensitivity and specificity of amylase at 3-fold above normal limit were 62.8% and 99.2% while those of lipase were 96.1% and 99.1% respectively. Both amylase and lipase had high accuracy index in the area under the ROC curve (0.990 and 0.997 respectively). Conclusions: In this study, serum lipase had better diagnostic accuracy as compared to serum amylase. In resource-constrained settings with limited lab and radiological facilities, serum lipase should be preferred over serum amylase for diagnosis of acute pancreatitis.